Why not XY? Male monoecious sexual phenotypes challenge the female monoecious paradigm in Cannabis sativa L. - Garcia-de Heer, Lennard; Mieog, Jos; Burn, Adam; Kretzschmar, Tobias (Frontiers in Plant Science, 2024)
Monoecy in Cannabis sativa L. has long been considered an industrially important trait due to the increased uniformity it offers and was thought to be exclusively associated with XX females. The isolation and characterisation of a monoecious individual with XY chromosomes sourced from non-proprietary germplasm is reported for the first time. The chromosomal make up of this trait was confirmed through inflorescence structure, growth habit, PCR analysis and sexual phenotypes of progeny from a series of targeted crosses. The identification of an XY monoecious phenotype widens our understanding of monoecy in Cannabis and has important implications for breeding, particularly for producing F1-hybrid seed.